N-Type Doped Silicon Thin Film on a Porous Cu Current Collector as the Negative Electrode for Li-Ion Batteries - Mukanova, Aliya; Nurpeissova, Arailym; Kim, Sung-Soo; Myronov, Maksym; Bakenov, Zhumabay (Chemistry Open, 2018)
This work reports the preparation of a three-dimensional Si thin film negative electrode employing a porous Cu current collector. A previously reported copper etching procedure was modified to develop the porous structures inside a 9 mm thick copper foil. Magnetron sputtering was used for the deposition of an n-type doped 400 nm thick amorphous Si thin film. Electrochemical cycling of the prepared anode confirmed the effectiveness of utilizing the approach. The designed Si thin film electrode retained a capacity of around 67 mAhcm@2 (1675 mAhg@1) in 100th cycle. The improved electrochemical performance resulted in an enhancement of both areal capacity and capacity retention in contrast with flat and rough current collectors that were prepared for comparison.